2001
DOI: 10.1063/1.1390305
|View full text |Cite
|
Sign up to set email alerts
|

Bond contraction and lone pair interaction at nitride surfaces

Abstract: Amorphous silicon nitride films of different composition deposited at room temperature by pulsed glow discharge plasma immersion ion implantation and depositionIt is shown that bond contraction and nonbonding lone-pair interaction dominate at nitride surfaces. The maximum elastic recovery of a nitride surface was found to be 100% under a relatively lower nanoindentation load (Ͻ1.0 mN) and the hardness of the surface was found to be 100% higher than the bulk value. It is interpreted that the spontaneous bond co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 24 publications
5
79
0
Order By: Relevance
“…Therefore, the enhanced intra-layer strength makes a nitride usually harder (~20 GPa), and the weakened inter-layer bonding makes the nitride highly elastic and self-lubricate. This mechanism also Nanoindentation profiles from TiCrN surface and sliding friction measurements from CN and TiN surfaces have confirmed the predicted high elasticity and high hardness at lower pressing load and the existence of the critical scratching load [99]. As compared in Fig.…”
Section: Solid Lubrication Due To Nonbonding Electron Polarizationsupporting
confidence: 62%
See 2 more Smart Citations
“…Therefore, the enhanced intra-layer strength makes a nitride usually harder (~20 GPa), and the weakened inter-layer bonding makes the nitride highly elastic and self-lubricate. This mechanism also Nanoindentation profiles from TiCrN surface and sliding friction measurements from CN and TiN surfaces have confirmed the predicted high elasticity and high hardness at lower pressing load and the existence of the critical scratching load [99]. As compared in Fig.…”
Section: Solid Lubrication Due To Nonbonding Electron Polarizationsupporting
confidence: 62%
“…As compared in Fig. 19(a), under 0.7 mN load of indentation, the elastic recoverability and hardness for a GaAlN film are higher than that of an amorphous carbon film [99]. The GaAlN surface is also much harder than the amorphous-C film under the lower indentation load.…”
Section: Solid Lubrication Due To Nonbonding Electron Polarizationmentioning
confidence: 67%
See 1 more Smart Citation
“…An examination of the hardness (also stress) and the Young's modulus using nanoindentation revealed that the surface of the TiCrN thin film (2 mm thick) is 100% higher than its bulk value [136]. The same trend holds for amorphous carbon [209] and AlGaN surfaces [210].…”
Section: 122mentioning
confidence: 57%
“…It has been discovered [132], with VLEED that the OeCu bond contraction (from 4% to 12%) forms one of the four essential stages of the OeCu(001) bond forming kinetics and, about 10% OeCu bond contraction for the OeCu(110) surface is necessary [133e135]. A 12e14% contraction of TiCrN surface has been confirmed by measuring the enhanced surface stress and Young's modulus of TiCrN films [136]. Theoretical calculations [137] confirmed that the interatomic distance drops significantly associated with rise of cohesive energy per bond as the dimensionality decreases from three to one for Ag, Au and Cu nanosolids, as shown in Fig.…”
Section: Monolayer Relaxationmentioning
confidence: 96%